2021
DOI: 10.1523/jneurosci.2527-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of Task Specificity for Visual and Tactile Sequences in the Auditory Cortex of the Deaf and Hard of Hearing

Abstract: It has been proposed that the auditory cortex in the deaf humans might undergo task-specific reorganization. However, evidence remains scarce as previous experiments used only two very specific tasks (temporal processing and face perception) in visual modality. Here, congenitally deaf/hard of hearing and hearing women and men were enrolled in an fMRI experiment as we sought to fill this evidence gap in two ways. First, we compared activation evoked by a temporal processing task performed in two different modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Moreover, analyses revealed a correlation between temporal discrimination task performance and the effect of disruption by STG-TMS at 180 ms: The better the behavioral performance, the larger the disruption induced by the STG-TMS at that time point. In a recent fMRI study, Zimmermann et al (2021) also found different results for temporal vs. spatial somatosensory processing in a group of deaf and hard-of-hearing participants ( n = 21). All participants were signers of Polish Sign Language (PJM), and their age of acquisition ranged from birth to primary school entry.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, analyses revealed a correlation between temporal discrimination task performance and the effect of disruption by STG-TMS at 180 ms: The better the behavioral performance, the larger the disruption induced by the STG-TMS at that time point. In a recent fMRI study, Zimmermann et al (2021) also found different results for temporal vs. spatial somatosensory processing in a group of deaf and hard-of-hearing participants ( n = 21). All participants were signers of Polish Sign Language (PJM), and their age of acquisition ranged from birth to primary school entry.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 89%
“…An interesting case of somatosensory processing in deaf and deafblind individuals are temporal tasks. Several studies have pointed to neural differences regarding spatial vs. temporal processing and the assumption that compared to hearing individuals, deaf individuals might show disadvantages in temporal processing (e.g., Heming and Brown, 2005;Bolognini et al, 2010Bolognini et al, , 2012Papagno et al, 2016;Zimmermann et al, 2021). Bolognini et al (2012) found a correlation between auditory cortex involvement latency and behavioral performance in a temporal task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, activations of the primary auditory cortex in the deaf induced by visual or tactile tasks are generally modest or absent. Various tasks, including language (MacSweeney et al, 2004), visual semantic task (Twomey, et al 2017) working memory (Cardin et al 2018) face recognition (Benetti, et al 2017), visual motion perception (Benetti, et al 2021) and tactile and visual sensory discrimination (Bola, et al 2017, Zimmermann, et al 2021) fail to evoke activation in A1. Analogously, the primary auditory cortex in the deaf cat also does not show effects of cross-modal reorganization (Kral et al, 2003(Kral et al, , 2017.…”
Section: Primary Auditory Cortex Of the Deaf Is 'Silent' During Visua...mentioning
confidence: 99%
“…These mechanisms are known to be right lateralized (Corbetta & Shulman, 2002). Task-based studies on deafness show significant right posterior STG activations for several attention-related functions and perceptual tasks such as spatial and temporal sequence discrimination (Bola et al, 2017;Zimmermann et al, 2021) visual motion detection (Benetti et al, 2021), visuo-spatial working memory (Ding, et. al…”
Section: Heterogeneity Across Hemispheresmentioning
confidence: 99%